Halal Certification and MSME Performance: A Bibliometric Perspective - Sari Utami; Azis Muslim; Muhammad Ghafur Wibowo (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
This study examines the evolving scientific landscape of halal certification and its implications for the performance of Micro, Small, and Medium Enterprises (MSMEs) within the expanding global halal economy. The growing importance of halal certification has transformed it from a religious compliance mechanism into a strategic instrument associated with consumer trust, market access, supply chain integrity, and business competitiveness. This research aims to synthesize the intellectual development, thematic evolution, and research trends related to halal certification and MSME performance through a bibliometric approach. Using a quantitative design, the study analyzed 598 documents indexed in the Scopus database from 2005–2024. Data collection employed the query Title-Abs-Key (“halal certification” AND (“MSME” OR “SME” OR “performance”)), while Biblioshiny and VOSviewer were utilized to map citation patterns, annual growth, collaboration networks, thematic clusters, and intellectual structures. The findings reveal that halal certification research has grown significantly, reflected in an annual growth rate of 28.37%, with Malaysia and Indonesia emerging as the dominant research hubs. The thematic focus has shifted from normative and theological discussions toward practical business dimensions, including consumer behavior, halal supply chain management, food safety, digital traceability, marketing, and economic competitiveness. The study also highlights the increasing integration of technology, such as blockchain systems, within halal certification mechanisms. These findings indicate that halal certification contributes not only to regulatory compliance but also to strengthening MSME competitiveness, improving consumer confidence, and expanding market opportunities. The study offers strategic implications for policymakers, industry stakeholders, and MSME actors in developing sustainable halal ecosystems and strengthening the global competitiveness of halal-certified enterprises. ABSTRAK - Sertifikasi Halal dan Kinerja UMKM: Perspektif Bibliometrik. Penelitian ini mengkaji perkembangan kajian ilmiah mengenai sertifikasi halal serta implikasinya terhadap kinerja Usaha Mikro, Kecil, dan Menengah (UMKM) dalam konteks ekonomi halal global yang terus berkembang. Sertifikasi halal tidak lagi dipahami semata sebagai bentuk kepatuhan religius, melainkan telah bertransformasi menjadi instrumen strategis yang berkontribusi pada peningkatan kepercayaan konsumen, perluasan akses pasar, penguatan integritas rantai pasok, dan peningkatan daya saing usaha. Penelitian ini bertujuan untuk mensintesis perkembangan intelektual, dinamika tema penelitian, serta arah kajian terkait sertifikasi halal dan kinerja UMKM melalui pendekatan bibliometrik. Metode yang digunakan bersifat kuantitatif dengan menganalisis 598 dokumen yang terindeks dalam basis data Scopus pada periode 2005–2024. Pengumpulan data dilakukan melalui kueri Title-Abs-Key (“halal certification” AND (“MSME” OR “SME” OR “performance”)), sementara analisis dilakukan menggunakan Biblioshiny dan VOSviewer untuk memetakan pola sitasi, pertumbuhan publikasi, jaringan kolaborasi ilmiah, klaster tematik, serta struktur intelektual penelitian. Hasil penelitian menunjukkan pertumbuhan kajian sertifikasi halal yang sangat pesat, dengan tingkat pertumbuhan tahunan sebesar 28,37%, serta menempatkan Malaysia dan Indonesia sebagai pusat utama penelitian global. Fokus kajian juga bergeser dari pendekatan normatif menuju isu-isu aplikatif, seperti perilaku konsumen, manajemen rantai pasok halal, keamanan pangan, ketertelusuran digital, pemasaran, dan integrasi teknologi, termasuk blockchain. Temuan ini menegaskan peran strategis sertifikasi halal dalam meningkatkan daya saing dan kinerja UMKM serta memperluas peluang pasar global.